OPM gradiometer for magnetorelaxometry - Prospero, A. [UNESP]; Miranda, J. R.A. [UNESP]; Baffa, O. (Springer Nature, 2022)
Magnetic nanoparticle (MNP) applications in biomedicine require the MNPs characterization, quantification, and spatial distribution determination. These are tasks that can be performed by magnetorelaxometry (MRX). Until recently, SQUIDs were the most commonly used sensors to detect MRX signals. Nowadays, a new commercial option is available: optically pumped magnetometers (OPMs). However, the commercially available OPMs systems present some limitations, especially regarding the MNP's relaxation characteristics. This chapter will review the use of OPMs for MRX measurements. The principles of MNP physics responsible for MRX signal production will be described, along with the procedures for MRX measurements and its application to biological process studies. The use of OPMs to perform MRX experiments and the development of a small-scale MRX-OPM system using two OPM magnetometers and a magnetically shielded chamber for sample analysis will also be discussed. Finally, we will present our point of view on future perspectives that can impact the use of OPMs in MRX measurements. Currently, OPMs present a good option for MRX measurements, mainly when it is possible to tune the relaxation times of MNPs to the time response of these devices.
Keywords: Brownian relaxation; Magnetic nanoparticles; Magnetorelaxometry; Néel relaxation; Optically pumped magnetometers